Persistent shallow magnetic inclination in the past 5 million years with implications for regional tectonics in the Philippines - Faustino-Eslava, Decibel V.; Shibuya, Hidetoshi; Dimalanta, Carla B.; Yumul, Graciano P.; Macuroy, Jonathan T. (Journal of Asian Earth Sciences: X, 2021)
[Display omitted] •A time-averaged geomagnetic field was derived from volcanic rocks in Luzon.•Rocks between 1 ka to 4.3 Ma consistently registered shallow inclination anomalies.•Inclination anomalies ranged between ~8° to 14° shallower than the GAD model.•The VGP scatter is comparable to other near-equatorial regions including Java. Despite the growing knowledge on geomagnetic paleosecular variations, the region around the Philippine archipelago remains to be a huge data gap in this regard. This work looked into rock magnetic information from <5 Ma volcanic rocks of Luzon Island to provide data for the statistical characterization of the time-averaged field in the region. A total of 21 sites with ages from 1 ka to 4.3 Ma yielded 13 normal, 7 reversed, and 1 intermediate polarity dataset. These were aggregated with previously published work to form a combined dataset of 59 normal + reversed sites with a mean virtual geomagnetic pole at 321.1°E and 83.7°N with α95 = 3.4, and an angular standard deviation of about 14.6°. This amount of scatter is slightly larger than that predicted by Model G but relatively comparable with other near-equatorial regions such as Java and Ecuador. This work is a first examination of paleomagnetic data from the Philippines in relation to the long-term behavior of the magnetic field in this part of Southeast Asia. The long-ranging shallow inclination observed may also have implications on how paleomagnetic data are interpreted for tectonic studies in the region.